Phytochemical profile, antioxidant, and antibacterial activities of Ipomoeae pes-caprae from Pantai Talang Siring Pamekasan, Madura: A promising source of natural bioactive compounds - Islamy, R Adharyan; Hasan, Veryl; Serdiati, Novalina; Kilawati, Yuni; Valen, Fitri Sil; Mutmainnah, Nurul (Genbinesia Journal of Biology, 2024)
This research investigates the phytochemical composition, antioxidant activity, and antibacterial efficacy of Ipomoea pes-caprae extracts collected from Pantai Talang Siring Pamekasan, Madura. Phytochemical analysis revealed the presence of alkaloids, flavonoids, phenolic compounds, terpenoids, tannins, and saponins in the extracts, indicating their rich bioactive profile. Antioxidant activity assessed via the DPPH assay demonstrated concentration-dependent scavenging of free radicals, with methanol and ethanol extracts exhibiting superior activity compared to the aqueous extract. Antibacterial assays against Escherichia coli and Staphylococcus aureus revealed significant inhibitory effects, with methanol and ethanol extracts displaying greater potency than the aqueous extract. These findings underscore the potential of Ipomoea pes-caprae as a source of natural antioxidants and antimicrobial agents, warranting further investigation into its pharmacological applications and therapeutic potential.